Muhammadiyah (Gerakan Sosial Keagamaan dan Pendidikan) - Gustia Tahir (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2010)
One of strategic way to develop moslem community is to change their static mindset to dynamic one. One of the way addresed by Ahmad Dahlan as Muhammadiyah Founder is through education system. In Dahlan’s opinion, education is very important. Therefore Muhammadiyah was established to realize the good educational system that can change the mindset. The main purpose of Muhammadiyah is to do Amar Ma’rum Nahi munkar, one of basic pillar of Islamic mission. For Muhammadiyah, education become the first priority to enlight moslem community. Beside that, Muhammadiyah not only focused on education, but social and economic aspect as well.